Deteksi Dini Risiko Stunting melalui Edukasi Kesehatan dan Pemeriksaan Fisik pada Balita - Sari, Dian Vita; Fatmawati, Fatmawati; Junaedy, Junaedy; Damayanti, Siti; Apriani, Fitri (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2026)
Background: Stunting remains one of the public health problems that requires early prevention through health education and growth monitoring in children under five years old. Lack of parental knowledge regarding balanced nutrition, child feeding practices, hygiene, and routine physical examination can increase the risk of growth disorders in toddlers. Purpose: Physical examination in toddlers is important to identify early signs of growth and developmental problems, including body weight, height or length, nutritional status, and general physical condition. Method: This community service activity was conducted face-to-face using health education, discussion, and direct physical examination methods. The stages of activity included preparation, delivery of educational materials about stunting, physical examination of toddlers, recording the results, and providing simple counseling to parents. Results: The activity showed that mothers were enthusiastic in participating in counseling and toddler physical examination. Before the education was given, several mothers still had limited understanding about the causes, impacts, and prevention of stunting. After the activity, mothers began to understand the importance of balanced nutrition, routine weighing, height measurement, immunization, hygiene, and regular visits to posyandu or health facilities. Conclusion: Education about stunting and physical examination of toddlers can increase parental awareness regarding early prevention of growth disorders. This activity is useful in encouraging families to monitor toddler growth regularly and implement healthy childcare practices.